2012
DOI: 10.1002/chem.201200733
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of D‐ and L‐Carbocyclic Nucleosides by Enzymatically Catalyzed Kinetic Resolution

Abstract: An efficient synthesis of (S)- or (R)-3-(benzyloxy-methyl)-cyclopent-3-enol was developed by appling an enzyme-catalyzed kinetic-resolution approach. This procedure allowed the syntheses of the enantiomeric building blocks (S)- and (R)-cyclopentenol with high optical purity (>98 % ee). In contrast to previous approaches, the key advantage of this procedure is that the resolution is done on the level of enantiomers that only contain one stereogenic center. Owing to this feature, it was possible to chemically co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…After hydrolysis under aqueous basic conditions, compounds 44 and 45 were isolated in 39% and 84% yields, respectively. 163 4.1.5. Synthesis via a 5′-H-Phosphonate Intermediate.…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…After hydrolysis under aqueous basic conditions, compounds 44 and 45 were isolated in 39% and 84% yields, respectively. 163 4.1.5. Synthesis via a 5′-H-Phosphonate Intermediate.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Under these restrictions, ATP, GTP, CTP, and UTP were obtained in 40− 65% yields, and carbocyclic nucleotides 150 and 151 (Figure 19) were synthesized in 18−19% yields. 163 6.1.5. Synthesis via a Phosphosulfonyl Intermediate.…”
Section: Nucleoside 5′-triphosphatesmentioning
confidence: 99%
“…When comparing the sugar puckering of natural nucleosides and carbocyclic nucleosides such as thymidine and carba -thymidine, it was found that the loss of the furanose oxygen in the carbocyclic nucleosides not only significantly decreased stereoelectronic effects, it also eliminated the anomeric effect as well as decreased important gauche interactions between the furan oxygen and the 3′ hydroxyl groups (Marquez, 1996; Marquez et al, 1996; Boyer et al, 2009; Mahler et al, 2012). As mentioned previously, these interactions typically influence the sugars into either a North or South conformation, or more commonly, an equilibrium of the two (Marquez, 1996; Marquez et al, 1996).…”
Section: Modifications To the Sugar Scaffoldmentioning
confidence: 99%
“…10 These promising data motivated us to develop an efficient, stereoselective, and convergent synthesis for 1′,2′-cis-disubstituted carbocyclic ribo-nucleoside analogues. With this strategy (Scheme 1), we succeeded in preparing a series of these compounds that were with sodium hydroxide in methanol worked in nearly quantitative yield (96%) and gave key intermediate 11 in an overall yield of 66% starting from (1R,2S)-2-(benzyloxymethyl)cyclopent-3-enol (7). The key step of our convergent strategy for synthesizing a series of 1′,2′-cis-disubstituted carbocyclic ribo-nucleoside analogues was the Mitsunobu coupling of different nucleobases or their precursors with cyclopentanol 11 (Table 1).…”
Section: Figure 1 Antiviral Active Carbocyclic Nucleosidesmentioning
confidence: 99%
“…Recently, we reported on the antiviral activity of carba-dT (3) in wild-type HIV-1 and in two multidrug-resistant HIV-1 clones (E2-2 and 8ka3). 7 Besides its promising potency against the wild-type HIV-1 strain, carba-dT has shown an increased antiviral effect against the mutant strains. Moreover, we recently showed that the antiviral activity of carba-dT could be increased by 15-fold (wild-type HIV-1) by application of our TriPPPro-approach.…”
mentioning
confidence: 99%